The Immunomodulation Effect of Staphyloxanthin Produced by Staphylococcus Aureus - Algabar, Fatima Amer Abd; Alwan, Ali Hussein; Khalaf, Khawlah Jebur; Authman, Sawsan Hassan (International Journal of Psychosocial Rehabilitation, 2020)
The results was indicated from a total of(70) isolate of staphylococcus (22.8%) isolated from 306 sample of different clinical sources that is primary diagnosis as S. aureus depending on cultural, morphological and biochemical test were collected from patients suffering from different disease infection such as wound ,UTI ,blood , eye , vagina , tonsil , nasal , burn infections and Bacteremia who had certain clinical. And the burn, wound and Nasal infection was the most accessible site for S. aureus (30.8 ,30.8,29.8)% respectively .the results was indicated the skim milk agar was the best medium of staphyloxanthin production , therefore the optimum condition of pigment production at 37°C for 72 hr .the extraction of staphyloxanthin was recorded highly significant by ethyl acetate and ethanol method . the column chromatography method used to purification of staphyloxanthin extract. as well as the results was recorded the antimodultory effect of staphyloxanthin (crude and partied in vivo and increasing in level of cytokines that induced by extracts effect). Conclusion: Staphyloxanthin acts as anti-oxidant ,anti-inflammatory ,as well as the carotenoid molecules could play an important role in regulation of the immune response. therefore staphyloxanthin represented as antimodulater effect during infection .